Study on the Creep Constitutive Model of a Sandstone Rock under the Water-Rock Interaction - Zuosen Luo; Zuoxiang Zhu; Jianlin Li; Lehua Wang; Qiao Jiang; Jingyu Zhang; Eleyas Assefa; Huafeng Deng (Advances in Civil Engineering)
With the continuous construction of large-scale geotechnical engineering, more and more attention has been paid to the long-term stability of rock mass engineering, especially the problem of rock creep under the influence of water. Combined with the author’s previous research on the triaxial creep characteristics of sandstone under water-rock interaction, a nonlinear creep constitutive model was established to capture the degradation behavior of a sandstone rock due to cyclic wetting and drying of the reservoir water. Due to the limitations of the visco-elastoplastic model, a thorough modification was done to account the effect of the water-rock interaction on the mechanical degradation of the sandstone rock. Finally, the predicted results were proved to be in a good agreement with the experimental results. Moreover, the strong correlations between the predicted results and the experimental results show the effectiveness of the modified model to scrutinize the nonlinear creep behavior of sandstone rock. Relevant research results have important theoretical significance for the accurate prediction and effective control of the long-term stability of rock mass engineering under the influence of water-rock interaction.